Biodegradable polymers: an update on drug delivery in bone and cartilage diseases - Lima, Ana Cláudia Fernandes (2019)
Introduction: The unique structure of bone and cartilage makes the systemic delivery of free drugs to those connective tissues very challenging. Consequently, effective and targeted delivery for bone and cartilage is of utmost importance. Engineered biodegradable polymers enable designing carriers for a targeted and temporal controlled release of one or more drugs in concentrations within the therapeutic range. Also, tissue engineering strategies can allow drug delivery to advantageously promote the in situ tissue repair. Areas covered: This review article highlights various drug delivery systems (DDS) based on biodegradable biomaterials to treat bone and/or cartilage diseases. We will review their applications in osteoporosis, inflammatory arthritis (namely osteoarthritis and rheumatoid arthritis), cancer and bone and cartilage tissue engineering. Expert opinion: The increased knowledge about biomaterials science and of the pathophysiology of diseases, biomarkers, and targets as well as the development of innovative tools has led to the design of high value-added DDS. However, some challenges persist and are mainly related to an appropriate residence time and a controlled and sustained release over a prolonged period of time of the therapeutic agents. Additionally, the poor prediction value of some preclinical animal models hinders the translation of many formulations into the clinical practice.